2009
DOI: 10.2981/09-005
|View full text |Cite
|
Sign up to set email alerts
|

Nesting Ecology of Greater Sage‐Grouse Centrocercus urophasianus at the Eastern Edge of their Historic Distribution

Abstract: Greater sage-grouse Centrocercus urophasianus populations in North Dakota declined approximately 67% between 1965 and 2003, and the species is listed as a Priority Level 1 Species of Special Concern by the North Dakota Game and Fish Department. The habitat and ecology of the species at the eastern edge of its historical range is largely unknown. We investigated nest site selection by greater sage-grouse and nest survival in North Dakota during 2005 -2006. Sage-grouse selected nest sites in sagebrush Artemisia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 42 publications
4
23
0
Order By: Relevance
“…However, additional research is necessary to evaluate factors influencing the structure of Wyoming big sagebrush in this region. Findings from this study, and those of Herman-Brunson et al (2009) and Kaczor et al (2011a, b) regarding sagebrush height (20-38 cm) and sagebrush canopy cover (4.7-19.2%) suggest that sagebrush community structure may be limited by these causal mechanisms. By understanding the factors influencing sagebrush growth and structure in a region, management could focus on developing strategies that limit further degradation of sagebrush.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…However, additional research is necessary to evaluate factors influencing the structure of Wyoming big sagebrush in this region. Findings from this study, and those of Herman-Brunson et al (2009) and Kaczor et al (2011a, b) regarding sagebrush height (20-38 cm) and sagebrush canopy cover (4.7-19.2%) suggest that sagebrush community structure may be limited by these causal mechanisms. By understanding the factors influencing sagebrush growth and structure in a region, management could focus on developing strategies that limit further degradation of sagebrush.…”
Section: Discussionsupporting
confidence: 47%
“…In fact, sagebrush cover used during the winter in the Dakotas was considerably greater than during other critical periods (i.e., nesting and brood-rearing; Herman-Brunson et al 2009;Kaczor et al 2011a, b). Sagebrush cover was the primary factor sage-grouse selected for and was the highest ranked variable regardless of snow presence during winter.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Coates and Delehanty () found reduced shrub canopy cover favored nest depredation by common ravens ( Corvus corax ) and speculated high shrub interspaces likely increased nest visibility and nest discovery by ravens. Other studies (Herman‐Brunson et al , Kaczor et al , Lockyer ) have found shrub canopy cover at nest sites was lower compared to other portions of the sage‐grouse range but taller grass height likely compensated for reduced shrub canopy cover (Kaczor et al ). Aldridge and Brigham () also reported a lack of sagebrush cover at the northern fringe of the sage‐grouse range in Canada and hypothesized unsuitable nesting and brood‐rearing habitat contributed to decreases in productivity.…”
Section: Discussionmentioning
confidence: 94%
“…Grass height and visual obstruction was greater at nest sites than in the environment, indicating females selected sites with structurally more closed habitat for nesting. Similarly, visual obstruction was an important predictor of nest site selection for sage‐grouse occupying the eastern edge of the species distribution (Herman‐Brunson et al , Kaczor et al ). Although we used a spatial autoregressive model to indicate which local vegetative attributes influenced the distribution of nest sites within our study area, we recognize the spatial patterns of non‐stationarity we observed warrant further attention.…”
Section: Discussionmentioning
confidence: 99%
“…During our study, sage‐grouse selected areas providing the greatest available sagebrush cover within 500 m of their use sites. In fact, sagebrush cover used during the winter in the Dakotas was considerably greater than during other critical periods (i.e., nesting and brood‐rearing; Herman‐Brunson et al 2009; Kaczor et al 2011 a , b ). Sagebrush cover was the primary factor sage‐grouse selected for and was the highest ranked variable regardless of snow presence during winter.…”
Section: Discussionmentioning
confidence: 99%